Solvent-free N-alkylation of 1, 3, 5-triaza-7: phospha-adamantane (PTA). (27th May 2019) - Udvardy, Antal; Szolnoki, Csenge Tamara; Joó, Ferenc; Kathó, Ágnes
Abstract: 1, 3, 5-triaza-7-phosphaadamantane was alkylated under solvent-free conditions with CH3 I, CH3 -(CH2 )3 -Br, Br-(CH2 )4 -Br, OH-CH2 -CH2 Br, and CH3 CH2 OOCCH2 Br in a planetary ball mill with yields over 90%. Due to spontaneous resolution, both 1-(2-ethoxy-2-oxoethyl)-3, 5-diaza-1-azonia-3, 5-diaza-7-phosphaadamantane bromide (4 ) and (4-bromobutyl)-1-azonia-3, 5-diaza-7-phosphaadamantane bromide (5 ) were obtained in the solid state as conglomerates of enantiomorphic crystals. GRAPHICAL ABSTRACT: UF0001